Lesion segmentation in surgical and diagnostic applications: MICCAI 2022 Challenges, CuRIOUS 2022, KiPA 2022 and MELA 2022, held in conjunction with MICCAI 2022, Singapore, September 18-22, 2022 : proceedings - Xiao, Yiming; Yang, Guanyu; Song, Shuang (Lecture notes in computer science, 2023)
This book constitutes three challenges that were held in conjunction with the 25th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2022, which took place in Singapore in September 2022. The peer-reviewed 10 papers included in this volume stem from the following three challenges: Kidney Parsing Challenge 2022: Multi-Structure Segmentation for Renal Cancer Treatment (KiPA 2022) The 2022 Correction of Brain Shift with Intra-Operative Ultrasound-Segmentation Challenge (CuRIOUS-SEG 2022) The 2022 Mediastinal Lesion Analysis Challenge (MELA 2022)